Creating a positive learning environment - Hue, Ming-Tak (Hong Kong university Press, 2008)
Includes bibliographical references and indexes.; This book is about management of student conduct in the classroom, which is the number one area of concern of many teachers. The chapters include discussions and real-life cases with specific reference to the influences of Chinese culture on Hong Kong classrooms. Examples are provided to illustrate how positive learning environments can be created and maintained in the classroom. Topics covered include managing challenging behaviour, establishing classroom rules, conveying authority, and coping with bullying.